Pengaruh ESG score terhadap kinerja keuangan - Oktrivina, Amelia; Nelyumna, Nelyumna; Harnovinsah, Harnovinsah; Atikah, Salma; Sujana, Aaliyah Putri (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study examines the direct effect of ESG scores on corporate financial performance. It proposes a moderation model to refine this relationship. Analyzing 30 publicly listed companies reporting ESG metrics on the Indonesia Stock Exchange (IDX) from 2021 to 2023, we employ path analysis and Moderated Regression Analysis (MRA) to test moderation effects. The findings reveal a multidimensional ESG-financial performance relationship: (1) a positive impact on the Debt-to-Equity Ratio (DER), indicating enhanced access to sustainable financing; (2) a dynamic relationship with Net Profit Margin (NPM), suggesting evolving ESG-related tradeoffs between costs and benefits; and (3) insignificant effects on Gross Profit Margin (GPM) and Return on Assets (ROA). The moderation analysis reveals that firms with high NPM are more effective at leveraging ESG benefits for debt expansion. At the same time, the interaction between ESG and GPM facilitates sustainable financing, even with high gross margins. These results underscore the importance of strategic ESG integration, particularly in light of time-lag effects and project selectivity. For investors, this provides a valuable framework for evaluating the implications of ESG on capital structure. The study offers novel insights through the development of profitability-based moderation models and uncovers underexplored ESG-leverage mechanisms in emerging markets.